Rice breeding for salt tolerance - Sankar, P. Deepa; Saleh, M.A. Arabi Mohamed; Selvaraj, C. Immanuel (Research in Biotechnology, 2011)
Human exploitation of earth’s resources is leading to new problems day by day and hence newer methods are devised to overcome the same. One such case is breeding for abiotic stress, utilizing even non arable land, to feed the ever increasing population. A major stress leading to yield loss can be due to inland and coastal salinity. Rice is the most important cereal crop which feeds humans on earth. This review tries to analyse the efforts of breeders in minimising the effects of salt stress on the yield of rice crop.